A83 Road traffic injuries and Alcohol: Double jeopardy in Pacific Island nations fuelled by inequitably distributed determinants of health. Issue 2 (June 2015) - Ameratunga, Shanthi; Herman, Josephine; Wainiqolo, Iris; Kafoa, Berlin
Abstract: Background: Efforts to address the burden of road traffic injuries in Pacific Island countries and territories are theoretically based on initiatives identified by the global road safety community. However, common risk factors targeted, including drink driving, are poorly quantified with respect to contribution to injury-involved crashes and contextual factors that challenge preventive interventions. We investigated the contribution of alcohol to the population-based burden of serious injury-involved road crashes in Fiji (second largest Pacific Island nation). We examine the findings in light of social determinants of health and injury, and the implications for future policy initiatives. Methods: We undertook an analysis of the Traffic-Related Injury in the Pacific (TRIP) project funded by the Wellcome Trust and Health Research Council of New Zealand. Specifically, a case-control study of four-wheeled motor vehicles was conducted in Viti Levu, Fiji in 2004/5 involving crash vehicles (recruited through a study specific hospital surveillance system) and a representative sample of control vehicles (recruited from road side surveys). Key informants for the study (drivers of the vehicles) completed standardised self-report surveys. Logistic regression analyses examined the association between alcohol and road traffic injuries, adjusting for relevant confounders. The findings were evaluated and interpreted applying the World Health Organization's Priority Public Health Conditions Analytical Framework. Results: The case control study involving 140 crash vehicles and 752 control vehicles revealed the three-fold excess in the odds of serious injury-involved crashes (resulting in hospital admission or death of a road user) associated with the consumption of alcohol within the 12 h prior to driving (Adjusted Odds Ratio 3.2; 95% confidence interval: 1.1-9.4). Using the Priority Public Health Conditions Analytical Framework, we identified important social parameters influencing inequities in the distribution of alcohol consumption and being a victim of road crashes in Pacific settings. In particular, we found differential distributions in socioeconomic position, exposure to alcohol, vulnerabilities to injury, and related outcomes. Conclusions: Alcohol imposes a substantial contribution to the burden of road traffic injury in the Pacific. However, there are several impediments to addressing this problem due to the inequitable distribution of alcohol exposure and road injury which are systemic, avoidable, unfair, and unjust. These findings highlight the imperatives to strengthen policies that address root causes of road injury embedded in inadequately regulated motorization, marketing and supply of alcohol, deficiencies in implementing drink-driving legislation and systemic improvements in transport infrastructure.